A corpus-based investigation on noun phrase complexity in L1 and L2 English writing. (July 2022) - Lan, Ge; Zhang, Qiusi; Lucas, Kyle; Sun, Yachao; Gao, Jie
Abstract: Since the 1990s, grammatical complexity has received considerable attention in different fields of L2 studies, for instance, second language acquisition (SLA) and L2 writing. While over the past three decades grammatical complexity has frequently been represented by clausal structures in L2 writing, since the beginning of the 2010s scholars have increasingly paid attention to phrasal features. We conducted this study to investigate how the use of noun phrases is associated with L1- and L2-English language backgrounds in academic writing. Noun phrase complexity was operationalized to the 11 noun modifiers (e.g., premodifying nouns, relative clauses, prepositional phrases) proposed in Biber, Gray and Poonpon (2011). A Chi-square test followed by a residual analysis was used to statistically analyze noun phrases in the two corpora. The results demonstrate that there is an association between the use of noun phrases and whether the author is an L1 or L2 user of English. The L1 essays have diverse patterns of noun phrases, whereas the L2 essays have compressed structures of noun phrases. A qualitative analysis of the corpora reveals repeated cases of phrasal modifiers in the L2 essays. Pedagogical implications are provided for academic writing courses for L1 and L2 students. Highlights: NP complexity is associated with L1- and L2-English language backgrounds. Eight noun modifiers contribute to this association in academic writing. L1 students produce diverse NP patterns with a wide range of noun modifiers. L2 students construct compressed NPs based on phrasal modifiers. L2 students use repeated cases of phrasal modifiers in their writing.